Temperature and humidity effects on performance of high and low yielding dairy sheep and goats - Serradilla J.M.; Ramón M.; Abo-Shady H.M.; Molina A.; Pérez-Guzman M.D.; Díaz C.; Carabaño M.J. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
A total of 49,918 and 1,176,670 test-day records belonging to 8,231 lactating goats and 177,605 lactating ewes, respectively, were used to study the response of Spanish dairy goats (Florida breed) and sheep (Manchega breed) to heat stress. The productive traits which were controlled include daily milk, fat and protein yields. The tolerance threshold and the slope of the response of these traits to thermal stress have been calculated. Test day records from each herd were merged with maximum and average daily temperature and a temperature-humidity index (THI) registered in weather stations the day of milk recording. Two sets of data were analysed: data from high milk yielding animals and data from low milk yielding animals. Two thresholds were found, one for low temperatures and the other for high temperatures. Climatic effects on yields were less marked in ewes compared to goats. Small differences were found between high and low productive animals in respect to thresholds and slopes, except for the reduction of fat and protein yields due to heat stress.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)